Analysis of the thoracic and abdominal mobility in elderly through computer photogrammetry - Oliveira, Nayara Priscila Dantas de; Pereira, Silvana Alves; Cruz, Maria do Socorro Luna; Andrade, Luiz Eduardo Lima de; Dantas, Thaissa Hamana de Macedo; Correia, Grasiela Nascimento; Dantas, Diego de Sousa (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Computerized photogrammetry has become a promising aspect for respiratory analysis, being a technology of low cost, good reproducibility and accuracy, compatible with the Brazilian public health situation. Objectives: To verify the applicability of the computerized photogrammetry method for analysis of thoracoabdominal mobility in the elderly. Methods: This is a methodological study, performed with 16 elderly women from Santa Cruz, RN, Brazil. Morphofunctional evaluation of body mass, stature, body mass index and thoracoabdominal mobility were performed through the computerized photogrammetry, whose technique was based on the capture of images at the maximum ventilation moments (maximal inspiration and expiration followed by apnea) of the elderly. For the delimitation of the thoracic wall were used 20mm diameter markers positioned at specific anatomical points, and the images were treated through the irregular quadrilaterals system in the AutoCAD 2007 Software. Results: Using computerized photogrammetry was possible to identify areas of compartments and sub-compartments of the thoracic wall with higher values at the inspiratory moment when compared to the expiratory moment, and with a greater contribution of the thoracic compartment in the pulmonary ventilation process of the elderly at the inspiratory moment. In addition, in the studied sample there was a higher prevalence of overweight elderly women (56%). Computerized photogrammetry was sensitive to the nutritional status of these elderly women, presenting areas of the abdominal compartment and sub-compartments with values higher than those presented by the elderly women with low weight. Conclusions: Computerized photogrammetry proved to be an effective and reliable technique for the thoracoabdominal mobility analysis of elderly women.v